Effect of feeding on the pharmacokinetics of oral minocycline in healthy research dogs. Issue 6 (18th August 2015) - Hnot, Melanie L.; Cole, Lynette K.; Lorch, Gwendolen; Rajala‐Schultz, Paivi J.; Papich, Mark G.
Abstract : Background: The effect of food on minocycline oral absorption in dogs is unknown. Objective: The objective was to determine the pharmacokinetics of minocycline after administration of a single oral dose in fed and fasted dogs. Methods: Ten research hounds were administered oral minocycline (approximately 5 mg/kg) with and without food, in a crossover study, with a one‐week wash‐out between treatments. Blood samples were collected immediately prior to minocycline administration and over 24 h. Minocycline plasma drug concentrations were measured using high‐performance liquid chromatography using ultraviolet detection and were analysed with compartmental modelling to determine primary pharmacokinetic parameters. Each dog was analysed independently, followed by calculation of means and variation of the dogs. The Wilcoxon signed–rank test [analysing secondary pharmacokinetic parameters – peak concentration ( C MAX ), area under the concentration versus time curve (AUC)] was used to compare the two groups. A population pharmacokinetic modelling approach was performed using nonlinear mixed effects modelling of primary parameters for the population as fixed effects and the difference between subjects as a random effect. Covariate analysis was used to identify the source of variability in the population. Results: No significant difference was found between treatments for AUC ( P  = 0.0645), although AUC was higher in fasted dogs. A significant difference was found for C MAX ( P  = 0.0059), with fasted dogs attaining a higher C MAX . The covariate of fed versus fasted accounted for a significant variation in the pharmacokinetics. Conclusions and clinical importance: Because feeding was a significant source of variation for the population's primary pharmacokinetic parameters and fasted dogs had higher minocycline concentrations, we recommend administering minocycline without food. Abstract : Background — The effect of food on minocycline oral absorption in dogs is unknown.Hypothesis/Objectives — The objective was to determine the pharmacokinetics of minocycline after administration of a single oral dose in fed and fasted dogs.Conclusions and clinical importance — Since feeding was a significant source of variation for the population's primary pharmacokinetic parameters and fasted dogs had higher minocycline concentrations, we recommend administering minocycline without food.